Analysis of Effects of Rough Strip Energy Dissipator on Hydraulic Property of Bend Flow. (7th October 2022) - Zhang, Honghong; Mu, Zhenwei; Fan, Fan; Li, Fanqi
Abstract : Installing rough strip energy dissipators (R-SEDs) at the bottom of curved spillways can facilitate energy dissipation and flow stabilization. In this study, the effects of R-SEDs set at the bottom of a 60° bend in a spillway were examined. This spillway had a large width-to-depth ratio (B / H > 5 ). Based on physical model tests, the distribution of hydraulic properties of the spillway under different runs was studied and analyzed. The results show that the R-SEDs effectively improved the flow pattern in the bend. The R-SEDs reduced the average dimensionless flow velocity by about 37.9% by increasing the roughness at the bottom of the bend. The energy dissipation rate of the R-SED decreased with an increase in discharge flow rate and ranged between 30% and 50%. These indicate that it is feasible to apply the R-SEDs to 60° bends of spillways with a large width-to-depth ratio at low-flow runs (the   tested   discharge   flow   rate = 15   L / s ). These results will provide a theoretical basis for the R-SED design of similar curved spillways.